P-Chlorophenol Removal In Sequencing Batch Biofilm Reactor - Mohamad, Muna Mastura (2011)
The objective of this study is to compare the performance of sequencing batch biofilm reactor (SBBR) and sequencing batch reactor (SBR) in treating p-chlorophenol (PCP) and nitrogen. The SBR and SBBR systems were operated in five sequential periods, namely FILL, REACT (aerobic and anoxic), SETTLE, DRAW and IDLE in the time ratio of 2:12:1:1:8 for a cycle time of 24 h. The SBR was used as the control reactor (RC) while the other two SBBRs, RB1 and RB2, were operated with 3 and 5% (v/v) of polyurethane foam cubes as the carrier materials, respectively.